Thermodynamics of binary gas adsorption in nanopores. Issue 35 (17th August 2016) - Dutta, Sujeet; Lefort, Ronan; Morineau, Denis; Mhanna, Ramona; Merdrignac-Conanec, Odile; Saint-Jalmes, Arnaud; Leclercq, Théo
Abstract : MCM-41 nanoporous silicas show a very high selectivity for monoalcohols over aprotic molecules during adsorption of a binary mixture in the gas phase. Abstract : MCM-41 nanoporous silicas show a very high selectivity for monoalcohols over aprotic molecules during adsorption of a binary mixture in the gas phase. We present here an original use of gravimetric vapour sorption isotherms to characterize the role played by the alcohol hydrogen-bonding network in the adsorption process. Beyond simple selectivity, vapour sorption isotherms measured for various compositions help to completely unravel at the molecular level the step by step adsorption mechanism of the binary system in the nanoporous solid, from the first monolayers to the complete liquid condensation.